Lipid droplet biosynthesis impairment through dgat2 inhibition sensitizes mcf7 breast cancer cells to radiation - Nisticò, Clelia; Pagliari, Francesca; Chiarella, Emanuela; Fernandes Guerreiro, Joana; Marafioti, Maria Grazia; Aversa, Ilenia; Genard, Geraldine; Hanley, Rachel; Garcia-Calderón, Daniel; Bond, Heather Mandy; Mesuraca, Maria; Tirinato, Luca; et al. (International journal of molecular sciences, 2021)
Breast cancer is the most frequent cancer in women worldwide and late diagnosis often adversely affects the prognosis of the disease. Radiotherapy is commonly used to treat breast cancer, reducing the risk of recurrence after surgery. However, the eradication of radioresistant cancer cells, including cancer stem cells, remains the main challenge of radiotherapy. Recently, lipid droplets (LDs) have been proposed as functional markers of cancer stem cells, also being involved in increased cell tumorigenicity. LD biogenesis is a multistep process requiring various enzymes, including Diacylglycerol acyltransferase 2 (DGAT2). In this context, we evaluated the effect of PF-06424439, a selective DGAT2 inhibitor, on MCF7 breast cancer cells exposed to X-rays. Our results demonstrated that 72 h of PF-06424439 treatment reduced LD content and inhibited cell migration, without affecting cell proliferation. Interestingly, PF-06424439 pre-treatment followed by radiation was able to enhance radiosensitivity of MCF7 cells. In addition, the combined treatment negatively interfered with lipid metabolism-related genes, as well as with EMT gene expression, and modulated the expression of typical markers associated with the CSC-like phenotype. These findings suggest that PF-06424439 pre-treatment coupled to X-ray exposure might potentiate breast cancer cell radiosensitivity and potentially improve the radiotherapy effectiveness.
Published 18 September 2021
Gesehen am 21.02.2022